2020
DOI: 10.1155/2020/3894309
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Endotoxin Induces Oxidative Stress and Reduces Milk Protein Expression and Hypoxia in the Mouse Mammary Gland

Abstract: The aim of this study was to investigate the mechanisms underlying the reduced milk production during mastitis. We hypothesized that bacterial endotoxin induces hypoxia, oxidative stress, and cell apoptosis while inhibiting milk gene expression in the mammary gland. To test this hypothesis, the left and right sides of the 4th pair of mouse mammary glands were alternatively injected with either lipopolysaccharide (LPS, E. coli 055: B5, 100 μL of 0.2 mg/mL) or sterile PBS through the teat meatus 3 days postpartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…Research has found that subclinical mastitis affected protein composition of milk [ 16 ], and LPS-induced mastitis affected the expression of milk protein genes (Csn1s1 and Csn2) [ 17 ]. Therefore, we investigated whether LPS challenge and Nrf2 genotype affected milk composition.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that subclinical mastitis affected protein composition of milk [ 16 ], and LPS-induced mastitis affected the expression of milk protein genes (Csn1s1 and Csn2) [ 17 ]. Therefore, we investigated whether LPS challenge and Nrf2 genotype affected milk composition.…”
Section: Discussionmentioning
confidence: 99%
“…1A). It is known that LPS inoculation results in a dramatic increment of polymorphonuclear leukocytes (PMN) in ltration into the lumen of milk alveoli, (Spitzer et al 2020), and generates ROS which is associated with lipid peroxidation resulting in oxidative damage of polyunsaturated fatty acids making them more susceptible to oxidation (Carvalho-Sombra et al), generating a genotoxic breakdown by-product known as MDA (Colagar et al 2009) which could inhibit the anti-oxidant molecules, inducing oxidative stress. In the contrast, nanocurcumin represses the formation of MDA regarding the e cient property of curcumin to scavenge lipid peroxide radicals such as ROS, superoxide radicals nitric oxide radicals, and hydrogen peroxide; due to its electron-donating phenolic hydroxyl group.…”
Section: Discussionmentioning
confidence: 99%
“…1 revealed that LPS stimulated MG tissue showed, decreased total GSH level which has been illustrated by a signi cantly increased GSH/GSSG ratio in comparison to the healthy rats, which is consequent to a higher GSSG level above the reduced GSH, and which are reversed under the in uence of nanocurcumin. The production of reactive species is generally mediated by several pathways including the peroxisomal oxidation of fatty acids, and oxidative bursts in immune cells (Spitzer et al 2020). As result, oxidative stress leads to macromolecular damages including proteins, lipids, and DNA, particularly, mitochondrial DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Mastitis has also been shown to induce lactation insufficiency in women. 13 In addition, the localized proinflammatory response can cause significant oxidative stress in the affected mammary gland 14 and lead to permanent tissue damage. Both reactive oxygen and reactive nitrogen species appear to be involved in this process.…”
Section: Introductionmentioning
confidence: 99%
“…Both reactive oxygen and reactive nitrogen species appear to be involved in this process. 15 , 16 The precise roles that localized and systemic responses play in the recovery and long-term prognosis of the disease are not currently well established. For example, while mastitis increases the risk of developing breast cancer in women, this increased risk is not limited to the area affected by mastitis, suggesting implication of the systemic inflammatory response rather than direct tissue damage.…”
Section: Introductionmentioning
confidence: 99%